Commentary. Pau Vila and the Territorial Division of Catalonia - Albet i Mas, Abel (Geopolítica(s). Revista de estudios sobre espacio y poder, 2025)
According to Pau Vila—an eminent teacher, pedagogue, and geographer—although the regional dimension has existed for centuries, it was only in the mid-19th century that it began to be considered the essential basis for Catalonia’s political and administrative territorial division. This coincided with the first signs of the recovery of self-government and, especially, with the rejection of the provincial structure by both citizens and elites. In 1931, the Catalan autonomous government created a Committee of scholars tasked with designing a territorial division that would serve the administration, management, and governance of the country. This Committee, led by Vila, ignored earlier debates based on the traditional (natural, historical) region and proposed a novel working methodology grounded in Vidalian geography and, above all, in the functional (urban, economic, relational) aspects of the territory. Surveys and visits to town halls helped shape a territorial division project that would only gain legal validation after the revolutionary outbreak of July 1936. The complex and turbulent context of the revolution and the war did not prevent its implementation or its widespread popular acceptance. Despite the repression exercised for decades by the Franco dictatorship, the «Pau Vila» regional division map became an icon of democratic resistance and national